2021
DOI: 10.1371/journal.pone.0249329
|View full text |Cite
|
Sign up to set email alerts
|

The presence of radioactive heavy minerals in prospecting trenches and concomitant occupational exposure

Abstract: Uranium, perhaps the most strategically important component of heavy minerals, finds particular significance in the nuclear industry. In prospecting trenches, the radioactivity of 238U and 232Th provides a good signature of the presence of heavy minerals. In the work herein, the activity concentrations of several key primordial radionuclides (238U, 232Th, and 40K) were measured in prospecting trenches (each of the latter being of approximately the same geometry and physical situation). All of these are located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Assuming equilibrium between uranium and radium, the mean of the 232 Th/ 226 Ra ratio in the examined samples of magmatic rocks was less than the mean worldwide value of crustal rocks, 3.94 [ 15 ]. The lowest results contributed to the high Ra content relative to Th in the studied samples, reflecting Ra mobility relative to Th, especially in the secondary environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming equilibrium between uranium and radium, the mean of the 232 Th/ 226 Ra ratio in the examined samples of magmatic rocks was less than the mean worldwide value of crustal rocks, 3.94 [ 15 ]. The lowest results contributed to the high Ra content relative to Th in the studied samples, reflecting Ra mobility relative to Th, especially in the secondary environment.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the leaching of uranium minerals (uranophane, uraninite, and betauranophane) through rainwater aids in their migration and precipitation along joints and faults [30]. Assuming equilibrium between uranium and radium, the mean of the 232 Th/ 226 Ra ratio in the examined samples of magmatic rocks was less than the mean worldwide value of crustal rocks, 3.94 [15]. The lowest results contributed to the high Ra content relative to Th in the studied samples, reflecting Ra mobility relative to Th, especially in the secondary environment.…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows that the activity concentration of the 238 U series included 234m Pa that varied from 217.9 to 1135 Bq/kg and 234 As demonstrated in Table 5, the concentrations of all the samples were very high compared to the worldwide average, except 235 U, which is lower than the worldwide average. The average worldwide radioelement values are 32 Bq/kg for 226 Ra, 45 Bq/kg for 232 Th, and 412 Bq/kg for 40 K [2]. The 226 Ra/ 238 U for the samples were around the unity, which suggested that Abu Rusheid granites are characterized by secular uranium equilibrium.…”
Section: Radiometric Evaluation Of the Studied Areasmentioning
confidence: 88%
“…Natural radioactivity in the environment is due to the presence of natural radionuclides, namely 238 U, 232 Th and 40 K, in various geological formations [1,2]. Terrestrial radiation comprises radiation emitted from these radionuclides and their progeny.…”
Section: Introductionmentioning
confidence: 99%